2020
DOI: 10.18203/2349-2902.isj20203778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgical Apgar score in predicting post-laparotomy complications

Abstract: Background: Surgical Apgar score is a simple, objective and economical ten point post-operative prognostic scoring system based on three readily recorded intra operative variables. Aim is to evaluate the applicability and accuracy of the surgical Apgar score in predicting post-operative complications and objectives are to identify patients at risk of developing post-operative complications based on intra-operative data, to study the incidence of post-operative complications and morbidity and mortality in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…This result is in line with the research by Masrudin et al (2017) which also had a cross-sectional research design and also used chi-square analysis, the aforementioned study showed = 0.002 (p <0.05) (Masrudin et al, 2017). Research by Ahmad & Kalsoom (2015), and Shah et al (2022) which compared the APGAR score between pregnant women with anemia and non-anemia also got the same results, namely chi-square of p = 0.012 (Ahmad & Kalsoom, 2015;Shah et al, 2020). However, the results of this study are not in line with research by Rahayu et al (2020) that there is no relationship between anemia in pregnant women and the APGAR score of newborns with the acquisition of the chi-square of p = 0.088 (p < 0.05) (Rahayu et al, 2020).…”
Section: Source: Secondary Data 2022mentioning
confidence: 76%
“…This result is in line with the research by Masrudin et al (2017) which also had a cross-sectional research design and also used chi-square analysis, the aforementioned study showed = 0.002 (p <0.05) (Masrudin et al, 2017). Research by Ahmad & Kalsoom (2015), and Shah et al (2022) which compared the APGAR score between pregnant women with anemia and non-anemia also got the same results, namely chi-square of p = 0.012 (Ahmad & Kalsoom, 2015;Shah et al, 2020). However, the results of this study are not in line with research by Rahayu et al (2020) that there is no relationship between anemia in pregnant women and the APGAR score of newborns with the acquisition of the chi-square of p = 0.088 (p < 0.05) (Rahayu et al, 2020).…”
Section: Source: Secondary Data 2022mentioning
confidence: 76%